Halal Tourism Development at Santen Sharia Beach, Banyuwangi: Opportunities, Challenges, and Sustainable Integration with Local Islamic Traditions - Endang Mintarja; Ali Masykur; Oneng Nurul Bariyah (Hayula: Jurnal Indonesia Studi Islam Multi-disiplin, 2026)
Halal tourism has emerged as a global competitiveness strategy, yet its implementation often faces a misalignment between global standards and local socio-cultural realities. This study analyzes the development of halal tourism at Santen Sharia Beach, Banyuwangi, through a qualitative approach. By integrating SWOT analysis with socio cultural and sustainability perspectives, we identify that the destination’s development is characterized by a "conceptual misalignment" between global inclusive discourse and local symbolic implementation. To resolve this, this study proposes a Glocalized Halal Tourism Governance Framework consisting of three interrelated dimensions: institutional integration, cultural embeddedness, and sustainability-oriented governance. The findings suggest that halal tourism is not merely a branding strategy but a complex governance model requiring the reconciliation of global Muslim-friendly frameworks with local cultural vernaculars. This study contributes to halal tourism scholarship by proposing a shift in analytical focus from market-oriented approaches toward a governance adaptation model, providing a preliminary conceptual reference for culturally diverse destinations.